2012
DOI: 10.1136/bcr-2012-007790
|View full text |Cite
|
Sign up to set email alerts
|

Polymer fume fever

Abstract: SUMMARYA 29-year-old Japanese man presented with fever, dyspnoea and non-productive cough after massive inhalation of evaporant from a polytetrafluoroethylenecoated cooking pan. Chest CT scan showed diffuse interstitial infiltration in both lungs. Based on the patient history, images and the pan he brought to the hospital, polymer fume fever was strongly suspected. His symptoms dramatically improved over the following 2 days after admission. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Shimizu et al [138] stated that PTFE can cause flu-like symptoms in humans-polymer fume fever. According to [139], polytetrafluoroethylene is of low oral toxicity, but ingestion can cause gastrointestinal tract irritation.…”
Section: Bindersmentioning
confidence: 99%
“…Shimizu et al [138] stated that PTFE can cause flu-like symptoms in humans-polymer fume fever. According to [139], polytetrafluoroethylene is of low oral toxicity, but ingestion can cause gastrointestinal tract irritation.…”
Section: Bindersmentioning
confidence: 99%
“…A small number of case studies have also reported more serious side effects of exposure to overheated Teflon, including lung damage. [9] Aluminum Cookware…”
Section: Health Hazards Develop Due To Non-stick Cookwarementioning
confidence: 99%
“…This is called "polymer fever" and there are more such examples in medical literature (Harris, 1951;Williams et al, 1974;Silver and Young, 1993). Because PTFE or Teflon is a commonly used compound that can lead to polymeric smoke fever when heated under poorly ventilated conditions, these cases are quite common (Adams, 1963;Delgado and Waksman, 2004;Son et al, 2006;Toyama et al, 2006;Shimizu et al, 2012). These cases of PFIB poisoning in the household or industry rarely end with death (Temple et al, 1985), however in view of the increasing use of PTFE in commercial and industrial products, recognition of this subject is important for doctors in the field of emergency medicine and doctors in the field of occupational medicine (Tsai et l., 2000; Stenton, 2016).…”
Section: Human Toxicitymentioning
confidence: 99%